Design and fabrication of small scale automatic chicken hatching machine - Tan, Chang Loke (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This project is about designing a fully automatic small scale chicken hatching machine. The increase in good population has caused the traditional incubation method unable to afford the demand of food required. Thus, the incubator is one of the ways that overcome the problem ststed.However, commercial incubator nowadays is expensivew for fully automated incubator and incdonvenien for the semi-automatic and manually incubator.